2021
DOI: 10.1016/j.ihj.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term oral anticoagulation for atrial fibrillation in low and middle income countries

Abstract: With increasing life-expectancy and changing demographics, non-valvular atrial fibrillation (AF) is currently the most common indication for long-term oral anticoagulation (OAC) in low and middle income countries (LMICs). Due to a decreasing trend in the prevalence of rheumatic heart disease (RHD), valve disease as a primary cause of AF now constitutes a small fraction of all people with AF. Moreover, emerging data also indicate that, patients with significant valve disease and AF may have a risk of stroke sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Differences seen might result from systemwide differences in management among regions because pf local AF guidelines, health care systems, or socioeconomic factors. 12 , 13 , 21 The high use of antiplatelet drugs in patients from Asia was previously reported. 22 , 23 , 24 , 25 Reasons are likely multifactorial.…”
Section: Discussionmentioning
confidence: 89%
“…Differences seen might result from systemwide differences in management among regions because pf local AF guidelines, health care systems, or socioeconomic factors. 12 , 13 , 21 The high use of antiplatelet drugs in patients from Asia was previously reported. 22 , 23 , 24 , 25 Reasons are likely multifactorial.…”
Section: Discussionmentioning
confidence: 89%
“…Atrial fibrillation detection should be increased through use of cardiac holters or wearable smart devices with proven diagnostic accuracy 39 . Atrial fibrillation diagnosis and management remains challenging in our setting, with the prohibitive costs of direct oral anticoagulants 40 , and low levels of access to affordable and reliable International Normalized Ratio (INR) monitoring to allow safe and effective warfarin prescription 41,42 . In hospital complications were associated with fatality and worse functional outcome, demonstrating the need to implement evidence based stroke care, such as stroke unit based care, inclusive of swallow screening for the prevention of aspiration pneumonia 15 .…”
Section: Discussionmentioning
confidence: 99%
“…38 Atrial fibrillation diagnosis and management remains challenging in our setting, with the prohibitive costs of direct oral anticoagulants, 39 and low levels of access to affordable and reliable International Normalized Ratio (INR) monitoring to allow safe and effective warfarin prescription. 40,41 In-hospital complications were associated with fatality and worse functional outcome, demonstrating the need to implement evidence-based stroke care, such as stroke unitbased care, inclusive of swallow screening for the prevention of aspiration pneumonia. 14 Our previous study found male sex to be associated with in-hospital fatality 14 ; we demonstrate this finding again for long-term fatality (HR: 1.28 (1.05-1.56)).…”
Section: Discussionmentioning
confidence: 99%
“…The inequalities in disease burden can partially be attributable to the treatment conditions, such as the use of new oral anticoagulants, left atrial appendage occlusion, and catheter or cryogenic balloon ablation, which are distributed unequally in different socioeconomic regions. 22,23 It is reported that patients living in the most deprived areas were 15% less likely to receive oral anticoagulation, compared to patients living in the least deprived areas. 24 In addition, population aging as well as some metabolic and behavioral risk factors, including diabetes, obesity, tobacco use, and sedentary lifestyle, tend to increase with development.…”
Section: Discussionmentioning
confidence: 99%
“…The AF/AFL burden was associated with the socioeconomic development and skewed more toward middle, low‐middle, and low‐SDI countries. The inequalities in disease burden can partially be attributable to the treatment conditions, such as the use of new oral anticoagulants, left atrial appendage occlusion, and catheter or cryogenic balloon ablation, which are distributed unequally in different socioeconomic regions 22,23 . It is reported that patients living in the most deprived areas were 15% less likely to receive oral anticoagulation, compared to patients living in the least deprived areas 24 .…”
Section: Discussionmentioning
confidence: 99%